PENGARUH MANAJEMEN KEWIRAUSAHAAN DALAM MENINGKATKAN OMSET DAN PRODUKTIVITAS KEWIRAUSAHAAN - Rachmawati, Susan (www.bsi.ac.id, 2014)
Entrepreneurship is an attempt by someone or a group of people to produce a product or a new and unique creativity by utilizing a variety of available resources as well as bold risk for his efforts. Whatever the form of the work done if not committed with a comprehensive plan that will lead to business growth are seen not as expected. Therefore, the author discusses the importance of entrepreneurial management in particular to increase productivity and turnover are owned, due to the increased productivity will boost turnover and the turnover increasing it will increase the amount of labor that would decrease the number of unemployed and will assist the government in providing jobs in ultimately will increase per capita income, which in turn some of the problems experienced by the State of Indonesia macro will be resolved. The method used in the study is secondary data which the authors take the example of a resource that has been successful in carrying out their entrepreneurial path from childhood up to produce a turnover of billions of dollars. Keywords: entrepreneurial management, productivity, turnover